HUBUNGAN HIGIENE MULUT TERHADAP TONSILITIS KRONIS PADA ANAK KELAS 5 DAN 6 DI MIN 04 PADANG. - Amri, Siti Salsabilla; Amir, Arni; Asyari, Ade (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Chronic tonsillitis in children may be caused by recurrent acute respiratory tract infection or untreated acute tonsillitis and other cofactors that can increase the risk of chronic tonsillitis such as poor oral hygiene Objective: The aim of this study is to know the the correlation between oral hygiene and chronic tonsillitis in 5th and 6th grades students in Madrasah Ibtidaiyah Negeri 04 Padang. Methods: This research is an analytical cross-sectional study. The samples included all 5th and 6th grades students in MIN 04 Padang who were fulfilled the inclusion criteria, with total 75 samples. The instruments used in the study include the oral hygiene questionnaire and tonsils examination. Data were analyzed by using Chi-square. Results : The result of the analysis showed the number of respondents with poor oral hygiene and chronic tonsillitis is 15 respondents (20%). Respondents with average oral hygiene and chronic tonsillitis is 13 respondents (17,3%), and 5 respondents (6,7%) had good oral hygiene and had chronic tonsillitis. The results have a significant relationship between the oral hygiene and chronic tonsillitis with a p value of 0.000 (<0.05). Conclusion: The conclusion of this study is that there was a significant relationship between the oral hygiene and chronic tonsillitis in 5th and 6th grades students in Madrasah Ibtidaiyah negeri 04 Padang